Utilização de resíduos da queima de biomassa para a produção de argamassa - Cardoso, Maurício de Freitas [UNESP] (2014)
A large amount of ash generated by burning of forest biomass, used by various branches of industry causes great concern due to their uncertain fate and its harmful consequences to the environment if disposed of incorrectly. Since this material has a high silica content is an alternative to its use as a substitute for sand. In the construction industry the use of sand is very common especially in the production of mortar and concrete. The amount of sand needed to fill this type of market is very large causing a huge demand for sand, which because it is a nonrenewable natural resource, generates major impacts on the environment due to its extraction. The aim was to study the feasibility of partial replacement of sand by wood ash, from the burning of biomass in the production of mortar for non-structural purposes. Initially an exploratory study was conducted to determine the water / cement more suitable for the specimens, due to the incorporation of new material regarding the mortar, as well as a chemical analysis of the ashes. Specimens with 0, 10% and 20% silica, from the ashes that were replaced in the sand regarding the mass of cement used were produced. Two cure times 7 and 28 days were used. To analyze the properties of the mortar axial compression and water absorption by capillarity tests were performed according to the recommendations of NBR 7215/97 and NBR 9779/12 respectively standards. Based on the analyzed results it is concluded that the incorporation of ash causes a decrease in resistance of the mortar, but if added in small amounts reduces the amount of water absorbed by capillarity